A hybrid DEM-SPH model for deformable landslide and its generated surge waves. (October 2017) - Tan, Hai; Chen, Shenghong
Highlights: A hybrid DEM-SPH model for studying landslide generated surge waves is presented. The δ-SPH algorithm is employed to eliminate spurious numerical noisy on the pressure field. Good agreement between numerical results and experimental data is obtained. The effect of landslide rigidity on wave characteristics is investigated. Short parametric sensitivity analysis is conducted to emphasize the importance of the lubrication of the grains. Abstract: Reservoir bank landslide and its generated surge waves are catastrophic hazards which may give rise to additional sedimentation, destroy hydraulic structures, and even cause fatalities. Since this process is very complex involving landslide impact, wave generation and propagation, it cannot be well captured with traditional numerical approaches. In this paper, a hybrid DEM-SPH model is presented to simulate landslide and to reproduce its generated surge waves. This model consists of discrete element method (DEM) for solid phase and smoothed particle hydrodynamics (SPH) for fluid phase as well as drag force and buoyancy for solid–fluid interaction. Meanwhile, the δ-SPH algorithm is employed to eliminate spurious numerical noise on the pressure field. Submarine rigid block slide is numerically tested to validate the proposed hybrid model, and the computed wave profiles exhibit a satisfactory agreement with the experiment. The hybrid model is further extended towards the submarine granular deformable slide which generates smaller and less violent surge waves. Kinetic and potential energy of both solid and fluid particle system are extracted to throw a light upon the process of landslide water interaction from an energy perspective. Finally, a sensitivity analysis on particle friction coefficient indicates that the lubrication of the solid particles is another important effect influencing the underwater landslide movement in addition to the drag effect. Graphical abstract: